Rational emotive behaviour therapy : 100 key points and techniques - Dryden, Windy; Neenan, Michael (London ; New York : Routledge, 2021)
"Rational Emotive Behaviour Therapy: 100 Key Points and Techniques presents 100 main features of Rational Emotive Behaviour Therapy (REBT) to help therapists improve their practice. This new edition has been updated throughout to take account of changes in the field and to be more consistent with the ideas of the authors which have been derived from their experience as trainers and supervisors of novice rational emotive behaviour therapists. Beginning with an introduction outlining the basics of the approach, this book offers thorough coverage of all the vital topics including: working alliance issues educational issues dealing with misconceptions about REBT encouraging clients to work at change dealing with obstacles to change using REBT creatively This concise and highly practical book will be invaluable to psychotherapists and counsellors in training and practice, ensuring a comprehensive understanding of the REBT approach"--
OCLC-licensed vendor bibliographic record.
Keywords: Rational emotive behavior therapy; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Emotions; PSYCHOLOGY / Psychotherapy / General